FEATURES OF EVALUATION OF ACCURACY OF GEODESIC GPS MEASUREMENTS - Voronkov, O.; Nesterenko, S.; Kasyanov, V. (Municipal economy of cities. Series: «Economy science», 2022)
It is known that the results of satellite measurements, which are obtained by the differential method, are usually dependent values and are characterized by the presence of a physical correlation with a close linear relationship. A model of errors of differential measurements is constructed, in which in order to separate the influence of interference on the signal coming to the satellite receiver, two components are identified, one of which is caused by interference from the main sources of error, are tropospheric and ionospheric refraction of navigation signals. individual measurement, in particular additional noise and multipath of satellite observation signals. The influence of the ratio of these components in the structure of measurement errors on the value of the correlation coefficient of signals received by satellite receivers operating in the differential mode is studied. According to the experience of satellite measurements, the share of the first component in the error of two synchronous measurements is more than 97 % of the total measurement error in the absence of additional external interference and multipath, and the correlation coefficient in practice is usually more than 0.999. This is confirmed by the fact that a pair of synchronous measurements are the result of measuring the same quantities, so their dependence is almost functional, it becomes probabilistic due to the influence of additional interference and multipath, which corresponds to the second component. Obviously, the effect of additional interference on the satellite signal path reduces the share of the first component in the measurement error. At the same time there is a decrease in the correlation coefficient. Analysis of the obtained data shows that in particular in the interval where the effect of additional interference, in particular the second component, does not exceed 25%, at 25% exposure the correlation coefficient takes 0.9, at 10% exposure it is 0.99, 3% exposure corresponds to a correlation coefficient of 0.9968. Therefore, the correlation coefficient is very sensitive to the influence of additional interference and multipath in the path of the radio signal, which is expressed by the second component in the error structure. This makes it possible to characterize each series of differential measurements by the presence or absence of multipath and justifies the use of reducing the correlation coefficient when performing coordinate determinations to indicate the presence of multipath on the useful signal of satellites.